(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Center’s flagship Aadhaar program has been ruled constitutionally lawful by the Supreme Court, but with restrictions. The exercise of completing the National Register for Citizens was started full fledges by the Government of Assam. Assam was among the three states where Aadhaar was not introduced, due to objections by student organizations, who insisted to complete National Register for Citizens first and then introduce Aadhaar. First draft of National Register for Citizens published in Dec 2017, which mentioned the names of 1.9 crore people as legal citizens out of 3.29 crore total applicants.